Residual current operated circuit-breakers with integral overcurrent protection for household and similar uses (RCBOs). Applicablity of the general rules to RCBOs. Applicability of the general rules to RCBOs functionally dependent on line voltage Part 2-2, (15th March 1995) - British Standards Institution,
No abstract available